Influence of Exsolved Volatiles on Reheating Silicic Magmas by Recharge and Consequences for Eruptive Style at Volcán Quizapu (Chile). (24th November 2017) - Degruyter, W.; Huber, C.; Bachmann, O.; Cooper, K. M.; Kent, A. J. R.
Abstract: The two most recent eruptions of Volcán Quizapu (southern Andes, Chile), only 85 years apart, were both triggered by magma recharge and extruded the same volume (about 5 km 3 ) of the same volatile‐rich dacitic magma, but showed a remarkable shift from effusive (1846–1847) to explosive (1932) behavior. We demonstrate, using a newly developed model, that the presence or absence of an exsolved volatile phase in the reservoir strongly influences its mechanical and thermal response to new inputs of magma. We propose that, prior to the 1846–1847 effusive eruption, gas bubbles damped the build‐up of excess pressure and allowed recharge of a significant volume of magma before triggering the 1846–1847 eruption. The strong temperature increase that resulted enhanced syneruptive outgassing leading to an effusive eruption. In contrast, during the repose period between the 1847 and 1932 eruptions, new recharges found a much less compressible host reservoir as the exsolved gas phase was largely removed in response to the prior eruption, yielding rapid pressurization, minor reheating, and comparatively less syneruptive outgassing. The combination of these effects culminated in an explosive eruption. Key Points: The presence of exsolved volatiles changes the thermal evolution of a magma reservoir Exsolved volatiles allow for a stronger temperature increase during recharge events leading up to eruption The eruptive style at Volcán Quizapu is explained through changes in exsolved volatile content in the magma chamber